PELAKSANAAN PENERTIBAN TANAH TERLANTAR BERDASARKAN PERATURAN PEMERINTAH NOMOR 11 TAHUN 2010 TENTANG PENERTIBAN DAN PENDAYAGUNAAN TANAH TERLANTAR (Studi Kasus di Kabupaten Sragen) - PRIHARTINI, PRIHARTINI (Dinamika Hukum, 2019)
The purpose of this study is to: 1) Review and analyze the implementation of curbing wastelands based on Government Regulation number 11 Year 2010 About Curbing and utilization of Wastelands in Sragen Regency. 2) review and analyze the barriers and solutions in the implementation of curbing wastelands based on Government Regulation number 11 Year 2010 About Curbing and utilization of Wastelands in Sragen Regency. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of second. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. The research results obtained the conclusion that the process of land reform they abandoned in Sragen is done through the following stages: (1) the determination of the object of wastelands, (2) identification and research, (3) a hearing Committee C, (4) Warning (I, II, III), and (5). Monitoring and evaluation on final warning (I, II, II).. The constraints on the face in law enforcement they would ground displaced in the Sragen Regency is as follows: (1) at the time of the hearing Committee C was not attended by the owner/holder of the right, (2) the sectoral Committee members Ego C in taking a stance, the Act of settlement, and the final decision. Problem resolution efforts undertaken in addressing constraints arising in the implementation of law enforcement they would ground displaced in Sragen Regency, namely (1) persuasive approach to holders in order to immediately implement the development in accordance with the circumstances or the nature and purpose of the grant of the right, (2) approaches the talks to members of the Committee C in order to recommend to the team to make way for Sragen permissions permissions required, members The Committee closed hearing without C attended by Holders so that the recommendations of the Committee C is based on the real conditions in the field. Keywords: Action, Wastelands.